2017
DOI: 10.1128/aac.01211-17
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Associations between Voriconazole Therapeutic Drug Monitoring, Toxicity, and Outcome in Liver Transplant Patients

Abstract: The aim of this study was to investigate the variability of the voriconazole plasma level and its relationships with clinical outcomes and adverse events among liver transplant recipients to optimize the efficacy and safety of their treatment. Liver transplant recipients treated with voriconazole were included, and voriconazole trough levels were quantified by a validated high-performance liquid chromatography method. Cytochrome P450 genotypes for CYP2C19 were evaluated in allograft liver tissues. A total of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
2
30
1
1
Order By: Relevance
“…This study found a clear association between voriconazole C min and AEs, and that the threshold C min for identifying patients with a higher risk of AEs was 5.12 mg/L, which is similar to the supratherapeutic target of voriconazole treatment recommended by the guideline from the British Society for Medical Mycology (12). The rate of AEs was higher in this study than previously reported in liver transplant patients (26). A particularly interestingly finding was that 69.0% (20/29) of cases of voriconazole-related AEs developed within the first week after voriconazole treatment, and that the elimination t 1/2 was prolonged, which suggested that implementing accurate initial dose or plasma concentration monitoring as early as possible could avoid the occurrence of AEs.…”
Section: Discussioncontrasting
confidence: 81%
“…This study found a clear association between voriconazole C min and AEs, and that the threshold C min for identifying patients with a higher risk of AEs was 5.12 mg/L, which is similar to the supratherapeutic target of voriconazole treatment recommended by the guideline from the British Society for Medical Mycology (12). The rate of AEs was higher in this study than previously reported in liver transplant patients (26). A particularly interestingly finding was that 69.0% (20/29) of cases of voriconazole-related AEs developed within the first week after voriconazole treatment, and that the elimination t 1/2 was prolonged, which suggested that implementing accurate initial dose or plasma concentration monitoring as early as possible could avoid the occurrence of AEs.…”
Section: Discussioncontrasting
confidence: 81%
“…This study identified a higher percentage of treatment success with voriconazole concentrations above 2 mg/L. Other authors that have analysed the relationship of the effect of the voriconazole concentration on the response to treatment of the IA have identified concentrations >2.0 mg/L in order to maximize the therapeutic potential of this drug . In our study, the lack of data on the minimum inhibitory concentration (MIC) has prevented analysing the impact of the pK/pD parameters in the treatment response.…”
Section: Discussionmentioning
confidence: 86%
“…11 tential of this drug. 30,31 In our study, the lack of data on the minimum inhibitory concentration (MIC) has prevented analysing the impact of the pK/pD parameters in the treatment response. However, some authors have suggested that a C min /MIC ratio from 2 to 5 is associated with a higher probability of response.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that CYP2C19 polymorphisms extensively affected voriconazole plasma concentration. 14,19,[48][49][50][51] A recent prospective study in renal transplant recipients 52 showed that CYP2C19 polymorphisms significantly affected the CL of voriconazole; PM patients had significantly higher plasma concentration than both IM patients and EM patients. However, CYP2C19 polymorphisms, it did not affect the pharmacokinetic parameters of voriconazole in this study.…”
Section: Discussionmentioning
confidence: 99%